Algoritmos de tributação e democracia: uma releitura do poder de tributar à luz da era da cibertransparência e das redes neurais artificiais - Teixeira Neto, Francisco Edilson (2022)
The usage of algorithms by the administrative political entities to assist them in the exercise of the taxing power brings about reflections on and theoretical questioning about the possibility of legal uncertainty and unconstitutionality in such usage. Firstly, because there are no specific rules governing the creation and usage of such tax algorithms; secondly, because there is no deliberative and democratic procedure that attests to the social acceptance of the usage of such technology; thirdly, algorithms, due to the biases and cognitive limitations of their programmers and developers, are flawed and bounded, even though there is potential for constant enhancement. In fact, some government agencies already employ algorithms in their inspection and collection activities, and these algorithms are developed or enhanced by information technology sectors belonging to government agencies or by legal persons governed by private law and created or contracted for this purpose. However, the usage of a sequence of executable acts that have the purpose of performing a certain task – or algorithm – by the administrative political entities is not preceded by a lawful cloak of legitimacy, an absence that stems, e.g., from the factual situation marked by the nonexistence of legal norms originated from the democratic system that regulate – as it has been pointed out – the production and usage of the aforementioned technological mechanism – the algorithm. In this context, e.g., the democratic principle, the principle of publicity, the principle of transparency and the legal certainty norm acquire very significant importance, since they can definitely assist in, firstly, the clarification of the factual and legal implications of the usage of tax algorithms, and, secondly, in the establishment of scientific and legal criteria that allow the government usage of these logical and computational executable sequences to have both greater legal certainty and greater adequacy to the social and legal arrangement and to the legal system; that is to say, those principles and boundaries could ensure that the usage of tax algorithms is based upon the currently accepted truth of the scientific and legal knowledge. In view of these initial pieces of information, during the course of this study, certain issues will be addressed throughout the process of producing solutions to theoretical and empirical problems, such as whether, in the development and improvement of these logical and computational structures, applicable for and employed in the exercise of the taxing power granted to the administrative political entities, there is or there is not the legal need for compliance with the democratic principles of publicity, transparency, and legal certainty – which has also constitutional aspect –, addressing, therefore, if such mechanism – the tax algorithm – of tax administration leads to a cloak of scientific and legal legitimacy. Therefore, the purpose and rationale for this study is the fact that it can affect both legally and socially a countless number of taxpayers and substitute taxpayers – those who are legally accountable for the payment of taxes on behalf of taxpayers themselves. It is an object of study that has legal, social, and consequently economic relevance. Regarding the methodological aspects, the methodology used in this study has been, as to the approach, of qualitative nature, since it has emphasized the understanding and interpretation of the subject and it has been made by means of compilation and critical analyses of theoretical and scientific texts. Consequently, as to the procedure, this study has been characterized by a bibliographic nature, given the actual need for determining cohesively and coherently the theoretical and practical premises of this study proposal. So much so that, to understand the subject, we have sought to investigate it through bibliographic research. Concerning the purpose and use of the results, this study has been "strategic basic", for its primary purpose has been the further development of the knowledge respecting the subject, as well as the possibility of using this study to solve problems of eventually applied research. With respect to the aims and goals, the study has been described as exploratory – because it primarily seeks the improvement of ideas – and descriptive – because it describes the situation at the time of the investigation, classifying and interpreting the facts.